Experimental Study and Numerical Analysis of Structural Performance of CRTS II Slab Track under Extreme High Temperature - Anxiang Song; Guowen Yao; Xuanrui Yu; Yuerui Wang; Yifei Wu (Advances in Materials Science and Engineering)
A ballastless track is susceptible to damage and even failure of structural components under the long-term effects of extremely high temperatures. In this paper, considering the influence of different constraint boundaries, a 1 : 4 scaled model of a ballastless track-bridge structural system was produced and placed in a large-sized environmental chamber. The thermal performance of the track structure was studied by carrying out temperature loading tests at extreme temperatures. In combination with the scaled-down model test data, a 3D nonlinear finite element model was established to investigate the damage evolution of broad-narrow joints under temperature gradient loading. The results are shown as follows: (1) the cement asphalt (CA) mortar layer has a hysteretic effect on the vertical temperature transfer. The most unfavorable structural part is between the track slab and the CA mortar layer of the track structure. (2) The constraint conditions accelerate the rate of temperature transfer, creating disturbances to the internal stresses of the track structure and amplifying the internal stresses induced by the environmental temperature increase. (3) Temperature and longitudinal stresses in the track’s structural layers are highly correlated. There is a significant quadratic regression between internal temperature and structural stresses in different extreme high-temperature environments. (4) As the temperature gradient load increases, the damage occurs at the junction of the broad-narrow joint and tends to expand towards the ends, which has little effect on the compression damage of the broad-narrow joint but significantly increases the tension damage. The research could provide useful guidance for the scientific operation and maintenance of the ballastless track in extreme high-temperature environments.